Severe nephrotic syndrome and early end-stage diabetic kidney disease in ABCC8-MODY12: A case report - Schmidt, Sophie H.; Barnas, Ursula; Aigner, Christof; Wolf, Peter; Kozakowski, Nicolas; Kain, Renate; Scherer, Thomas; Schmidt, Alice; Sunder-Plassmann, Gere (Frontiers in Genetics, 2023)
A 24-year old man with diabetes mellitus presented with advanced kidney disease and severe proteinuria. Genetic testing revealed ABCC8-MODY12 (OMIM 600509) and a kidney biopsy showed nodular glomerulosclerosis. Shortly thereafter he commenced dialysis and glycemic control improved on treatment with a sulfonylurea. Diabetic end-stage kidney disease in patients with ABCC8-MODY12 was not reported up until now. Thus, our case highlights the risk for early-onset and severe diabetic kidney disease in patients with ABCC8-MODY12 and the importance of timely genetic diagnosis in unusual cases of diabetes to allow for proper treatment and prevention of late sequelae of diabetes.